Identification of the major pregnancy-specific antigens of cattle and sheep as inactive members of the aspartic proteinase family. - Xie, S C (1991)
Pregnancy in cattle and sheep can be diagnosed by the presence of a conceptus-derived antigen in maternal serum that is secreted by trophoblast and placental tissue primarily as an acidic component of Mr 67,000. Molecular cloning of its cDNA reveals that the antigen belongs to the aspartic proteinase family and has greater than 50% amino acid sequence identity to pepsin, cathepsin D, and cathepsin E. The inferred sequences of the ovine and bovine polypeptides show approximately 73% identity to each other. Critical amino acid substitutions at the active site regions suggest that both proteins are enzymatically inactive. The antigen is a product of trophoblast binucleate cells that invade maternal endometrium at implantation sites.